JOM: The Journal 2025-2026 Editorial Calendar Is Open for Submissions - Kelly Markel (JOM, 2024)
Context Concussions are some of the most common sports-related injuries in US high school athletes, yet concussions have a wide range of symptoms and stigma that lead to underreporting of symptoms to healthcare professionals and coaches. Sustaining multiple concussions has been linked to neurological issues in both the short term and long term. It has also been proven that adequate sleep is essential for a variety of activities and cognitive functions. Previous studies have linked sleep disturbances to increased head injury risk in collegiate athletes, but less is known about this relationship in younger populations. Objectives With thousands of high school athletes sustaining concussions annually, this study aimed to explore associations between sleep quantity/quality and concussion history in high school athletes and if these vary by sex or other sociodemographic factors. Methods We conducted a cross-sectional analysis utilizing 2019-2021 Youth Risk Behavior Surveillance System (YRBSS) data. Participants included high school students who reported playing at least one sport and answered questions regarding sleep and concussions. Additional variables such as age, sex, race, and ethnicity were analyzed. We utilized binary and multivariable regression models to examine associations between sleep duration and concussion history. Results High school athletes averaged 6.56 h of sleep per night (95 % CI: 6.5 to 6.6). Each sociodemographic factor was independently associated with sleep duration. In adjusted regression models, athletes with one concussion slept less than those with none (-0.12 h; 95 % CI: -0.23 to -0.01). Those with two or more concussions reported even shorter sleep durations (-0.24 h; 95 % CI: -0.43 to -0.05). Conclusions A dose-response association was observed between the self-reported concussion history and the shorter self-reported sleep duration among high school athletes. The long-term clinical implications of these modest differences in sleep duration remain uncertain and warrant further investigation. Future longitudinal studies utilizing objective sleep and validated concussion assessments are needed to assess the long-term effects of concussion-related sleep disruption from adolescence into adulthood and to investigate potential causality in this relationship.